Body fat assessment in elite soccer players: cross-validation of different field methods. Issue 3 (3rd July 2018) - Suarez-Arrones, Luis; Petri, Cristian; Maldonado, Rafael Angel; Torreno, Nacho; Munguía-Izquierdo, Diego; Di Salvo, Valter; Méndez-Villanueva, Alberto
ABSTRACT: Objective: In soccer players, body fat mass (FM) is commonly estimated by assessment methods such as skinfolds, bioelectrical impedance analysis (BIA) and dual-energy X-ray absorptiometry (DXA). The main aim was to cross-validate the 3 field methods for quantifying body fat against a recent model of DXA.Methods: This study involved a group of 18 international-level, elite male soccer players belonging to the squad of a Serie A club in Italy.Results: All skinfold equations (with the exception of Deuremberg) showed large-to-very large positive correlations (r from 0.61 to 0.82, p ≤ 0.01) with DXA, however, BIA %FM data showed unclear relationship. All the sum of skinfolds showed moderate-to-very large positive correlations with DXA (r from 0.46 to 0.79, p values from 0.061 to 0.000). The combination of triceps and iliac crest skinfolds selected by the stepwise procedure explained 78.6% variance in DXA total %FM.Conclusion: All different methods employed in the present study are likely to differ, which prevent their use interchangeably. Almost all the equations showed positive correlations, but with different values in comparison with a recent model of DXA. Finally, the sum of skinfolds appears to be a good alternative when limited time and budged is available.